Heterogeneity of melts in impact deposits and implications for their origin (Ries suevite, Germany). (25th November 2018) - Siegert, Susann; Hecht, Lutz
Abstract: Impact melt‐bearing clastic deposits (suevites) are one of the most important records of the impact cratering process. A deeper understanding of their composition and formation is therefore essential. This study focuses on impact melt particles in suevite at Ries, Germany. Textures and chemical evidence indicate that the suevite contains three melt types that originate from different shock levels in the target. The most abundant melt type ("melt type 1") represents well‐mixed whole‐rock melting of crystalline basement and includes incompletely mixed mafic melt schlieren ("melt type 1 mafic"). Polymineralic melt type 2 comprises mixes between monomineralic melt types 3 and melt type 1. Melt types 2 and 3 are located within melt type 1 as small patches or schlieren but also isolated within the suevite matrix. The main melt type 1 is heterogeneous with respect to trace elements, varying geographically around the crater: in the western sector, it has lower values in trace elements, e.g., Ba, Zr, Th, and Ce, than in the eastern sector. The west–east zoning likely reflects the heterogeneous nature of crystalline basement target rocks with lower trace element contents, e.g., Ba, Zr, Th, and Ce, in the west compared to the east. The chemical zoning pattern of suevite melt type 1 indicates that mixing during ejection and emplacement occurred only on a local (hundreds of meters) scale. The incomplete larger scale mixing indicated by the preservation of these local chemical signatures, and schlieren corroborate the assumption that mixing, ejection, and quenching were very rapid, short‐lived processes.